Serum Citrulline and Ornithine: Potential Markers of Coeliac Disease Activity - Douda, Ladislav; Hyšpler, Radomír; Mžik, Martin; Vokurková, Doris; Drahošová, Marcela; Řeháček, Vít; Čermáková, Eva; Douda, Tomáš; Cyrany, Jiří; Fejfar, Tomáš; Jirkovský, Václav; Kopáčová, Marcela; et al. (Acta Medica, 2022)
INTRODUCTION: To date, there is not generally accepted and universal indicator of activity, and functional integrity of the small intestine in patients with coeliac disease. The aim of our study was to investigate whether serum concentrations of the non-essential amino acids citrulline and ornithine might have this function. METHODS: We examined serum citrulline and ornithine concentrations in a subgroup of patients with proven coeliac disease and healthy controls (blood donors). RESULTS: A total of 94 patients with coeliac disease (29 men, mean age 53 ± 18 years; 65 women, mean age 44 ± 14 years) and 35 healthy controls (blood donors) in whom coeliac disease was serologically excluded (10 men, mean age 51 ± 14 years; 25 women, mean age 46 ± 12 years) were included in the study. Significantly lower concentrations of serum ornithine were found in patients with coeliac disease (mean 65 ± 3 μmol/L; median 63 μmol/L, IQR 34 μmol/L, p < 0.001). No statistically nor clinically significant differences were found in the citrulline concentrations between the study and control group. CONCLUSIONS: Serum ornithine (but not citrulline) may be useful for assessing the functional status of the small intestine in uncomplicated coeliac disease. Further studies involving more detailed analysis of dietary and metabolic changes in patients will be needed to reach definitive conclusions.
Keywords: dospělí; Female; Adult; ženské pohlaví; Ornithine; lidé; Citrulline; dieta; ornithin; Male; Diet; citrulin; Aged; Celiac Disease; lidé středního věku; senioři; mužské pohlaví; Middle Aged; celiakie; Humans